Widespread Grylloblattid Insects After the End-Permian Mass Extinction - Zhang, Qianqi; Jarzembowski, Edmund A.; Wang, Bo (Frontiers in Earth Science, 2022)
The end-Permian mass extinction (EPME) led to a severe terrestrial ecosystem collapse. However, the ecological response of insects to the EPME remains poorly understood. Here, we report a new species assigned to Chauliodites, Chauliodites tongchuanensis sp. nov., (Grylloblattida: Chaulioditidae) from the Middle Triassic Tongchuan Formation of Shaanxi, northwestern China, redescribe Chauliodites fuyuanensis (Lin, 1978) from the Early Triassic Kayitou Formation of Yunnan, and Chauliodites nanshenghuensis comb. nov. from the Middle Triassic of Guizhou, southwestern China. Our results show that Chauliodites widely distributed after the EPME is probably related to the rise of isoetalean-dominated low-productivity terrestrial ecosystems.